2021
DOI: 10.1292/jvms.21-0353
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the microbiota of normal cow milk using MinION<sup>TM</sup> nanopore sequencing

Abstract: The aim of this study was to evaluate the microbiota of normal milk in dairy cows and their relationship with host factors, such as the age of the cow (Age), somatic cell counts in milk (SCCs), and days in milk (DIM). We investigated 48 milk samples from 22 cows with no systemic or local clinical signs using MinION TM nanopore sequencing for a 16S rRNA gene amplicon. Bacterial richness was positively correlated with the DIM (p = 0.043), and both the Shannon-Wiener Index and Simpson's Index, which are metrics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Enterococci are commonly found in the feces of pre-ruminant calves ( Devriese et al, 1992 ) and are facultatively anaerobic, lactic acid-producing bacteria that are capable of utilizing various sugars ( Švec and Devriese, 2015 ). Kocuria are typically associated with the skin microbial community and have been found among udder skin microbiota ( Braem et al, 2013 ) and in milk of cows ( Quigley et al, 2013 ; Shinozuka et al, 2021 ). The colostrum-related ASVs disappeared from the fecal community after weaning, which indicates that they had a functional role only during the pre-weaning period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enterococci are commonly found in the feces of pre-ruminant calves ( Devriese et al, 1992 ) and are facultatively anaerobic, lactic acid-producing bacteria that are capable of utilizing various sugars ( Švec and Devriese, 2015 ). Kocuria are typically associated with the skin microbial community and have been found among udder skin microbiota ( Braem et al, 2013 ) and in milk of cows ( Quigley et al, 2013 ; Shinozuka et al, 2021 ). The colostrum-related ASVs disappeared from the fecal community after weaning, which indicates that they had a functional role only during the pre-weaning period.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with milk bacteria, the milk archaea have been less studied. However, recent evidence suggests that there is a rich community of archaea in milk ( Hoque et al, 2019 ; Shinozuka et al, 2021 ), and archaea have also been found in the uterus ( Yeoman et al, 2018 ) and GI tract of calves right after birth ( Guzman et al, 2015 ). Our results suggest that colostrum could serve as a seeding source for some archaea, but the majority were seeded from young animal rumen early in life and remained in the large intestine thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive analysis of the microbiota in the milk samples was performed based on previously reported methods [ 46 ] as follows. DNA was previously isolated from each milk sample using ISOSPIN Fecal DNA (Nippon Gene, Tokyo, Japan) according to the manufacturer’s instructions that included an initial bead-beating step.…”
Section: Methodsmentioning
confidence: 99%
“…MinION sequencing is a promising approach for rapid diagnosis of pathogen and antibiotic resistance profiles as well as better clinical management of mastitis A growing body of literature emphasized the applicability of MinION sequencing and its advantages for the infectious disease diagnostics (Petersen et al, 2019;Mongan et al, 2020;Taxt et al, 2020;Avershina et al, 2021;Ciuffreda et al, 2021). However, the use of MinION sequencing in food microbiology and veterinary medicine fields so far has been very limited to a few studies (Catozzi et al, 2020;Azinheiro et al, 2021;Shinozuka et al, 2021). Identifying causative pathogens in mastitis-infected animals is a challenging task, and previous research has documented that some of the causative pathogens are not detectable using conventional diagnostic methods (Taponen et al, 2009;Kuehn et al, 2013;Addis et al, 2016).…”
Section: Effective Host Cell Depletion and Dna Degradation Improved T...mentioning
confidence: 99%